Impact of Land Property Rights Security Cognition on Farmland Quality Protection: Evidence from Chinese Farmers - Laiyou Zhou; Hua Lu; Jinlang Zou (Land, 2023)
The stability or security of property rights plays an important role in stimulating the investment of economic entities, which can prevent or alleviate the degradation of land resources and improve the efficiency of agricultural management. This paper focuses on the perspective of land property rights security awareness, analyzes its impact on farmers’ cultivated land quality protection behavior, and, on the basis of a theoretical analysis framework linking the two, uses farmer survey data from southern Jiangxi Province and the probit model to empirically analyze the impact of farmers’ land property rights security awareness on their cultivated land quality protection behavior. The results show that the improvement in farmers’ awareness of land property rights security could significantly improve their probability of applying farmyard manure. This conclusion is proven to be robust by means of a replacement model and adjustment variables. Moreover, it is found that the influence of land property rights security cognition on farmyard manure application differs among farmers by age, degree of part-time work and land scale. Finally, we can draw inspiration for improving the effective implementation of public policies and increasing the publicity of legal knowledge of land property rights to improve farmers’ awareness and consideration of land property rights security.